2018
DOI: 10.1515/aut-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Washing on Durability of Hydrophobic Finishes of Membrane Laminates

Abstract: The aim of the study is to show how the washing process, while considering the type of washing agent and number of wash cycles, determines the durability of hydrophobic finishes of laminated fabrics. The samples of material were subject to multiple wash cycles in clear water and with the use of two types of washing agents, namely, an ordinary washing powder and a detergent recommended by manufacturers of functional clothing. The washed materials were subject to spray test and its waterproofing and degree of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Moreover, this loss could be attributed to the peeling of some rGO sheets from the clusters due to the loss of the oxygenated functional groups. 28 It is noticeable that the mass percentages of Ag and O in Ag@GO-SA/PP/HNO 3 -IP are much lower than those of Ag@GO/PP/HNO 3 -IP and Ag@rGO/PP/HNO 3 -IP. The addition of long carbon chains of SA onto Ag@GO sheets has increased the mass of the fiber as well as the number of C while the amount of O and Ag molecules remains the same.…”
Section: Characterization Of Before and After Pretreated And Modified...mentioning
confidence: 92%
“…Moreover, this loss could be attributed to the peeling of some rGO sheets from the clusters due to the loss of the oxygenated functional groups. 28 It is noticeable that the mass percentages of Ag and O in Ag@GO-SA/PP/HNO 3 -IP are much lower than those of Ag@GO/PP/HNO 3 -IP and Ag@rGO/PP/HNO 3 -IP. The addition of long carbon chains of SA onto Ag@GO sheets has increased the mass of the fiber as well as the number of C while the amount of O and Ag molecules remains the same.…”
Section: Characterization Of Before and After Pretreated And Modified...mentioning
confidence: 92%
“…The influence of maintenance treatments on the reduction of the durability of hydrophobic finishes was also confirmed by Gargoubi et al [ 11 ], Schellenberger et al [ 12 ], Kowalski et al [ 22 ], Solomon [ 23 ], Yurdakul et al [ 24 ], Shi et al [ 25 ], Deng et al [ 26 ], and Ivanova and Zaretskaya [ 27 ], who observed that the deterioration of water-repellent properties of materials with hydrophobic finishes increases with the number of washing cycles. Additionally, it was shown that the durability of water-repellent properties of materials depends on the type of laundry detergent used [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the method adopted for testing the water repellency of materials, the conclusions drawn from the results obtained may differ significantly. Solomon [ 23 ], Yurdakul et al [ 24 ], Kowalski and Salerno-Kochan [ 28 ], and Brooks [ 30 ], who evaluated the durability of hydrophobic finishes using the spray test method, showed a significant decrease in the water-repellent properties of textiles after washing processes. In contrast, Shi et al [ 25 ], Deng et al [ 26 ], and Ivanova and Zaretskaya [ 27 ], who used the contact angle measurement method to evaluate the hydrophobic properties of materials after washing processes, showed a high durability of the tested hydrophobic finishes.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of biofouling the most commonly used solution is the introduction of silver nanoparticles into membranes or into a separate system [46,47]. These multiple solutions show that the problem is not yet fully solved, especially in particular cases where the flow regime cannot be imposed [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%